The Influence of Accounting Information System Quality and Work Motivation on Employee Performance - Rachman, Gun Gunawan; Juniarti, Senny Sri; Nurcholisah, Kania (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2024)
The quality of accounting information systems plays a crucial role in generating accurate accounting information, facilitating companies in their daily operations, and presenting reports effectively and efficiently. In an increasingly competitive environment, employee motivation becomes a primary factor in enhancing their performance, which positively impacts the company's competitiveness. Employees, as key elements, significantly influence the company's progress, prompting every organization to strive for improved performance. This study focused on a population of 355 employees from an electronic equipment distribution company. The sampling method involved distributing questionnaires using simple random sampling techniques, with a total of 110 respondents. The data collected were analyzed using SEM-PLS version 4.1.0.2. The findings indicate that: 1) the quality of the accounting information system has a significant effect on employee performance; 2) work motivation also contributes positively to employee performance. These findings emphasize the importance of improving accounting information systems and work motivation to enhance employee performance, ultimately supporting the sustainability of the company.